MODEL DASHBOARD MONITORING KINERJA PEGAWAI PADA TOP LEVEL MANAGEMENT - Sali Alas Majapahit; Asep Somantri; Roni Ilham Subagja (STMIK Mardira Indonesia, Bandung, 2021)
Human resources are one of the important factors in a company that must be managed by means of human resource management. One of the focuses on human resource management is by monitoring or monitoring the work carried out by each human resource, to ensure that the work carried out by each existing human resource is in accordance with the work targets that must be achieved. This research is to facilitate the Top Management in monitoring the development of employee performance, and facilitate Top Management in obtaining information related to the development of employee performance. The research was conducted by analyzing Top Managerial needs, looking for relevant KPIs and designing dashboards starting from setting dashboard functionalities, alerts, and dashboard interfaces. The results of this study are in the form of a dashboard design or model for monitoring employee performance. The results of the design can be used by the organization to help make decisions at the Top Management level. Key Word: Dashboard, Key Perfomance Indicator (KPI), Manajemen Kinerja pegawai, MonitoringDOI: 10.5281/zenodo.5784186